Can balance trampoline training promote motor coordination and balance performance in children with developmental coordination disorder?. (January 2015) - Giagazoglou, Paraskevi; Sidiropoulou, Maria; Mitsiou, Maria; Arabatzi, Fotini; Kellis, Eleftherios
Highlights: A 12 week balance trampoline training program was verified an effective intervention for improving motor coordination and balance performance. The performance improvements may be due to alterations in the complex sensory motor stimulation of training program. The participants' efforts to adapt to the trampoline unstable surface improved their balance and motor performance. Students with DCD require intervention programs with the use of interesting and attractive equipment. Abstract: The present study aimed to examine movement difficulties among typically developing 8- to 9-year-old elementary students in Greece and to investigate the possible effects of a balance training program to those children assessed with Developmental Coordination Disorder (DCD). The Body Coordination Test for Children (BCTC; Körperkoordinationstest fur Kinder, KTK, Kiphard & Schilling, 1974 ) was chosen for the purposes of this study and 20 children out of the total number of 200, exhibited motor difficulties indicating a probable DCD disorder. The 20 students diagnosed with DCD were equally separated into two groups where each individual of the experimental group was paired with an individual of the control group. The intervention group attended a 12-week balance training program while students of the second – control group followed the regular school schedule. All participants were tested prior to the start and after the end of the 12-week period by performing static balance control tasks while standing on an EPS pressure platform and structured observation of trampoline exercises while videotaping. The results indicated that after a 12-week balance training circuit including a trampoline station program, the intervention group improved both factors that were examined. In conclusion, balance training with the use of attractive equipment such as trampoline can be an effective intervention for improving functional outcomes and can be recommended as an alternative mode of physical activity.